FINANCIAL ACCOUNTING IN FAMILYFIRM: A BIBLIOMETRIC ANALYSIS OF EARNINGS MANAGEMENT, REPORTING QUALITY, AND AUDIT RESEARCH - Muhammad Adnan Effendi Putra; Trisna Gayatri; Deasy Emalia (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the development, structure, and patterns of research on financial accounting in family firms, focusing on earnings management, reporting quality, and audit research. The research method used was a bibliometric analysis of 162 open-access documents indexed by Scopus for the period 2007–2026. The analysis was conducted using performance analysis and science mapping with the help of Scopus, Microsoft Excel, and VOSviewer to identify publication trends, author productivity, country contributions, influential journals, most-cited documents, and relationships between keywords. The results show that research on financial accounting in family firms has increased significantly, especially after 2020, with key emerging themes including earnings management, family ownership, financial reporting quality, corporate governance, and audit quality. Keyword co-occurrence analysis yielded six research clusters demonstrating the interrelationships between earnings management, financial reporting quality, governance, accounting conservatism, and audit mechanisms. This study concludes that the literature on financial accounting in family firms continues to develop and is still dominated by issues of accounting information quality, the influence of family ownership on reporting behavior, and the role of governance and audit mechanisms in enhancing the credibility of financial reports. Keywords: Audit Quality, Earnings Management, Family Firms, Financial Reporting Quality, Financial Accounting